The Influence of Religiosity and Self-Compassion on the Psychological Well-Being of Unmarried Early Adult Men in The Batak Tribe - Pasaribu, Ronald Panaehan; Brahmana, Karina Meriem Beru; Rosito, Asina Christina; Gea, Berkat Sudianto; Siringoringo, Nova V (Universitas Ahmad Dahlan, 2024)
In the patrilineal culture of the Batak tribe, marriage is a societal expectation for adult men, and remaining unmarried can lead to significant pressure, resulting in feelings of frustration and failure. Religiosity and self-compassion are believed to positively impact the psychological well-being of unmarried early adult men within the Batak tribe. This study aims to explore the influence of religiosity and self-compassion on the psychological well-being of these men. The research involved 66 participants who were early adult, unmarried, and of Batak ethnicity. The instruments used in the study included scales for religiosity, self-compassion, and psychological well-being, with data analyzed through multiple regression analysis. The findings indicate that: 1) religiosity does not significantly influence psychological well-being, and 2) selfcompassion has a positive impact on psychological well-being. It is recommended that unmarried early adult men in the Batak tribe enhance their self-compassion by cultivating positive self-assessment and self-respect in various situations, particularly in response to the stress of being unmarried